Vandetanib as a potential treatment for breast cancer. (September 2014) - De Luca, Antonella; D'Alessio, Amelia; Maiello, Monica Rosaria; Gallo, Marianna; Bevilacqua, Simona; Frezzetti, Daniela; Morabito, Alessandro; Perrone, Francesco; Normanno, Nicola
<x xml:space="preserve">Abstract</x> Introduction: The VEGF A /VEGF receptor (VEGFR) network actively contributes to breast cancer pathogenesis and progression, playing a pivotal role in promoting tumour-associated angiogenesis. <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=Vandetanib&logicalOpe1=OR&field2=articletitle&text2=Vandetanib&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">Vandetanib is a multitargeted tyrosine kinase inhibitor that selectively blocks VEGFR-2, the EGFR and RET tyrosine kinases. The drug has shown promising anti-tumour activity in preclinical models of breast cancer. Areas covered: The authors summarise the data on pharmacodynamics, pharmacokinetics, preclinical and clinical studies of vandetanib up to April 2014, using: the PubMed and the clinicaltrials.gov databases; the FDA and EMA websites and the ASCO proceedings. Expert opinion: Vandetanib has demonstrated a modest efficacy in patients with metastatic breast cancer. In this respect, the increased number of angiogenic pathways activated during tumour progression might partially explain the intrinsic and acquired resistance to the drug in advanced breast cancer. The activity of vandetanib in early phases of the disease, and in combination with other anti-angiogenic factors or metronomic therapy, should be explored in order to improve the clinical efficacy of the drug. Finally, the identification of predictive markers might help to select patients who are more likely to respond to anti-angiogenic drugs.